Experimental study on the synergistic effect of gas extinguishing agents and water mist on suppressing lithium-ion battery fires. (December 2020) - Zhang, Lin; Li, Yongqi; Duan, Qiangling; Chen, Man; Xu, Jiajia; Zhao, Chunpeng; Sun, Jinhua; Wang, Qingsong
Highlights: An improved fire extinguishing method was proposed. Synergistic effect of gas agents and water mist on LIB fire was studied. Gas agents reduce thermal buoyancy, to facilitate the water mist cool effectively. Abstract: Currently, effective suppression methods are still required to deal with lithium-ion battery (LIB) fires. In this paper, a novel synergistic fire extinguishing method of gas extinguishing agent (C6 F12 O, CO2 and HFC-227ea) and water mist is designed to evaluate the effect of their combination. A 243 Ah large-scale LIB with LiFePO4 as cathode is used in this work. Several cell parameters are measured to evaluate the suppression effect of fire extinguishing method, such as extinguishing time, maximum temperature, mass loss and heat release rate. Meanwhile, the cooling effect, fire extinguishing effect and economic benefit of different fire extinguishing methods are all considered. Results show that the suppression effect of synergistic fire extinguishing method is better than that of the single agent. Single application of water mist can hardly extinguish the flame, while the combination of gas extinguishing agents and water mist can extinguish the flame finally. However, the C6 F12 O extinguishes the flame immediately, while CO2 has a longer extinguishing time, and HFC-227ea cannot extinguish the flame. So in these experiments, the C6 F12 O combined with water mist exhibits the best extinguishing and cooling effect. The CO2 combined with water mist has good economic benefit, better fire extinguishing effect and cooling effect in these experiments, which can also be considered in suppressing LiFePO4 LIB fires.